Vibration mechanisms of spur gear pair in healthy and fault states. (15th December 2016) - Li, Yongzhuo; Ding, Kang; He, Guolin; Lin, Huibin
Abstract: The vibration frequency components of gear system are complicated and changeful, some of those are even hard to explain. Based on the dynamic equations of a single-stage gear pair and some reasonable simplifications, frequency responses of the gear pair in healthy state and those suffering from different faults are analyzed, respectively. The excitation sources of vibration frequency components such as rotational frequency harmonics, mesh frequency harmonics, modulation sidebands and resonance frequency bands are investigated accordingly. The causes of the asymmetrical modulation sidebands around the mesh frequency harmonics, which are commonly appeared in the vibration spectrum of gear system, are explained. The effectiveness of the theoretical deductions is confirmed by dynamic simulations and experimental results. Highlights: Vibration mechanisms are analyzed based on the dynamic equations. The complicated frequency components of gear system are analyzed. The phenomenon of asymmetrical modulation sidebands is explained. The effectiveness is confirmed by simulations and experimental results.